Pengaruh Karakteristik Sosial Ekonomi Terhadap Skala Usaha Sapi Potong Di Desa Itterung Kecamatan Tellusiattinge - Maryam, Maryam; Nurfaida, Nurfaida; Herni, Herni; Farid, Muhammad; Puspitasari, Ita; Bonewati, Yulia Irwina (Anoa: Journal of Animal Husbandry, 2024)
Business scale is one of the keys to developing livestock businesses to support the national meat self-sufficiency program. If the scale of the farmer's business increases, the cattle population will also increase. This research aims to determine the influence of socio-economic characteristics on the scale of beef cattle businesses in Itterung Village, Tellusiattinge Regency. This research was conducted from July to August 2021 with the consideration that in Itterung Village, the population of cattle is largest. The type of research used is explanatory quantitative research. The number of breeders in Itterung Village was 72 people selected as research samples. This research method uses data analysis using the F test and t test using a multiple linear regression model with the help of the SPSS 23 program. The research result show that capital (X1), land (X3), food (X4), education level (X6 ), number of family members (X7), farmer experience (X8), and farmer motivation (X9) have a significant effect P<0.005 on the scale of beef cattle farming business (Y) while livestock breeds (X2), age (X5), perception of farming (X10), extension intensity (X11) and livestock ownership status (X12) have no significant effect P>0.005 on the scale of beef cattle farming business (Y).